DEVELOPMENT OF AESTHETIC CULTURE OF STUDENTS IN THE CIRCLES OF RANGTASVIR (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the importance of discipline in the development of students' aesthetic culture, the development of students' aesthetic culture, and the aesthetic culture of students in color The developer is detailed about the essence and functions of the educational process aimed at any purpose.